ASUHAN KEBIDANAN KELUARGA BERENCANA AKSEPTOR BARU KB IUD: SEBUAH LAPORAN KASUS - Juariah, Juariah; Pratama, Aurelia; Fauzia, Fauzia (Politeknik Kesehatan Kemenkes Bandung, 2025)
The Intrauterine Device (IUD) was the effective, safe, and reversible long-term contraceptive method. Despite its numerous advantages, IUD adoption still faces challenges such as a lack of information about IUDs, negative public perceptions, misconceptions, and side effects. If IUD side effects are not properly managed, they can cause anxiety and unpreparedness, potentially leading to complications, leading to premature IUD removal. The purpose of this Final Project Report is to provide family planning midwifery care to Mrs. S, 39 years old, P3A0, a new IUD recipient.This report uses a midwifery care approach with documentation using the SOAP (Subjective, Objective, Analysis, and Management) approach. Data were collected through history taking, physical examination, observation, documentation, and literature review.The subjective data assessment revealed that Mrs. S complained of vaginal discharge, no itching, no odor, and abdominal pain three days after IUD insertion. The pain scale used a Numeric Rating Scale (NRS) instrument with a scale of 5. Objective data from a genital examination revealed a white, watery vaginal discharge. Mrs. S, 39 years old, P3A0, a new IUD acceptor, was analyzed. The management provided included providing information about IUDs, conducting genital and IUD examinations, explaining the causes of vaginal discharge and abdominal pain, advising on maintaining personal hygiene, teaching deep breathing relaxation techniques, and recommending warm compresses on the painful abdominal area. The conclusion from the care provided to Mrs. S was that the mother understood the IUD, no longer experienced vaginal discharge or abdominal pain, and was not worried about her condition.